Pembuatan Media Promosi E-Booklet dengan Aplikasi Canva Pro pada PT Angkasa Pura I Juanda Surabaya - Cici Dewi Sekartaji; Joni Dwi Pribadi (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aimed to develop an effective promotional e-Booklet using Canva Pro for PT Angkasa Pura I Juanda Surabaya, specifically for the human remains lounge in the cargo business area, which previously utilized a market-sounding PowerPoint presentation. The research method employed was Action Research, consisting of planning, action, observation, and reflection. Data collection was conducted through observation, interviews, documentation, and questionnaires. The questionnaire was distributed to 17 respondents, comprising 1 manager, 2 relevant staff members, 2 design experts, 2 marketing experts, and 10 prospective customers, with the effectiveness of the e-Booklet analyzed using the EPIC Model. The result of this study was an e-Booklet created using Canva Pro, which proved to be a highly effective promotional tool for PT Angkasa Pura I Juanda, achieving a final EPIC Rate of 4.51. The implication of this research is that the developed e-Booklet can be utilized as a promotional medium by being integrated into the company's official website to further convince prospective customers.